Behavioral intention to use biopesticides among rice farmers in Indonesia - Istriningsih; Sumarwan Ujang; Hartoyo; Suharjo Budi (E3S Web of Conferences)
The adoption rates of biopesticides by Indonesian farmers are still low, despite their benefits to the environment. The purpose of this study is to examine the determinants of non-user rice farmers’ intentions to utilize biopesticide products, based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). It focuses on the variables that influence their intention to use biopesticides. A modified UTAUT 2 model was applied, incorporating five key variables: performance expectancy, followed by effort expectancy, along with social influence, in addition to facilitating conditions, and finally price value. Data were collected from 400 rice farmers in Bogor Regency, West Java, Indonesia. Structural equation modeling (SEM) was applied to analyze the data. The results show that all five variables influence non-user rice farmers’ intentions to use biopesticides. In addition, the UTAUT 2 model explained 39% of the variance in intention. Practical recommendations include enhancing farmer training, promoting peer recommendations, and developing pricing strategies to improve the perceived value of biopesticides.